Keeping Faith. Series 2 [videorecording (DVD)] - Broughton, Pip; Freegard, Bradley, 1983-; Edwards, Aimee-Ffion, 1987-; Daniel, Hannah, 1986- (Acorn, 2020)
Eighteen months ago, mother-of-three Faith had her cozy life thrown into chaos after the disappearance of her husband, Evan. Still striving to keep her family together, Faith must fulfill Evan's debt to a vicious crime family even as she fights her attraction to a former client. Then a local farmer is found dead, and his wife, Madlen, is arrested for his murder.